Resveratrol and β-hydroxy-β-methylbutyric acid supplementation promotes ileal development and digestive function by altering microbial community abundance and metabolites in Tibetan sheep - Gan, Jiacheng; Ji, Qiurong; Su, Quyangangmao; Hou, Shengzhen; Gui, Linsheng (Frontiers in Veterinary Science, 2024)
IntroductionThe effects of resveratrol (RES) and β-hydroxy-β-methylbutyric acid (HMB) on phenotype, immunity, digestive enzyme activity and short-chain fatty acids (SCFAs) contents in ileum of Tibetan sheep were investigated.MethodsA total of 120 two-month-old Tibetan sheep (15.5 ± 0.14 kg) were randomly allocated to 4 treatments: control group (basal diet), RES group (basal diet +1.5 g RES/d), HMB group (basal diet +1.25 g HMB/d), RES-HMB group (basal diet +1.5 g RES/d + 1.25 g HMB/d).ResultsResults indicated that dietary RES and (or) HMB supplementation significantly improved the phenotype (mucosal thickness and villus width), SCFAs concentrations, and digestive enzymes (lipase, cellulase, and α-amylase) (p < 0.05). The relative abundance of Brevibacillus, Clostridium sensu stricto 3, and Eubacterium hallii group were increased, while the abundance of Ruminococcus and Mogibacterium were decreased (p < 0.05) in the RES-HMB group. The metabolic profiling indicated an increase in the differential metabolites (DMs) including L-arginine, butanoic acid, D-mannose, and retinol were increased in the RES-HMB group (p < 0.05).DiscussionIn summary, our results suggested that RES and (or) HMB supplementation improved SCFAs concentration by up-regulating the microbial community abundance (Brevibacillus, Clostridium sensu stricto 3, and Eubacterium hallii group) and metabolism (L-arginine, butanoic acid, D-mannose, and retinol), thus contributing to ileal morphology and digestive enzyme activity. These findings may provides a novel reference for the nutritional regulation to improve the production of Tibetan sheep.